Growth traits of the Dorper sheep. I. Factors influencing growth traits - Inyangala, B.A.O.; Rege, J.E.O.; Itulya, S. (1992)
Data on 969 Dorper lambs collected over a 10-year period (1978 to 1987) at Ol'Magogo were used in this study. Lamb traits studied were weights from birth to yearling and absolute growth rates between adjacent stages of growth. All the fixed effects studied influenced growth in one way or another. Sex was highly significant for all traits (P<0.01) except growth rates between weaning and six months (GR2), and six to nine months (GR3), and season of birth influenced all traits significantly (P<0.05) except birthweight (BIRTHW), growth rates between weaning and six months (GR2), and between nine and twelve months (GR4). The effect of parity was confined to pre-weaning traits (P<0.05), while period of birth was significant (P<0.05) on all traits except yearling weight (ADJTMW) and growth rate between weaning and six months (GR2).